2020
DOI: 10.1088/1755-1315/457/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Sub-population survey of Dipterocarpus retusus Bl. in Mount Gede Pangrango National Park

Abstract: Dipterocarpaceae are globally important tree family due to its conservation status. Most of Dipterocarpaceae in Java are distributed in lowland area. However, several species exist in higher altitude such as Gede Pangrango National Park (GPNP) area. All Dipterocarpaceae species in GPNP are vulnerable or endangered based on IUCN Red List status. Dipterocarpaceae species are main priorities for plant conservation in GPNP. In this study we conducted early survey of Dipterocarpus retusus Bl. sub-population in Bodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…The present study, along with Helmy et al (2009) and Sadili (2014), has described the transitional forest area between the lowland and montane forests with tree species diversity that was not known when GGPNP was established in 1980. It is interesting to note that species of Dipterocarpaceae were reported to occur spa-ringly in Bodogol (Ismail et al, 2000;Helmi et al, 2009;Junaedi et al, 2020) but they were not found in the present study plots, possibly because of unsuitable microclimate and located far away from the seed producing mature trees (Purwaningsih, 2004).…”
Section: Species Compositionmentioning
confidence: 53%
See 2 more Smart Citations
“…The present study, along with Helmy et al (2009) and Sadili (2014), has described the transitional forest area between the lowland and montane forests with tree species diversity that was not known when GGPNP was established in 1980. It is interesting to note that species of Dipterocarpaceae were reported to occur spa-ringly in Bodogol (Ismail et al, 2000;Helmi et al, 2009;Junaedi et al, 2020) but they were not found in the present study plots, possibly because of unsuitable microclimate and located far away from the seed producing mature trees (Purwaningsih, 2004).…”
Section: Species Compositionmentioning
confidence: 53%
“…The GGPNP was divided into several resorts (regions), including the Bodogol Resort (BR) for management purposes. BR covers planted forests, natural upper lowland forests with an elevation of < 1,000 m asl, and montane forests with an elevation > 1,000 m asl (Sadili et al, 2008;Sadili & Alhamd, 2012;Sadili, 2014;Junaedi et al, 2020). We know very little about the structure and composition of the lowland forests in GGPNP and to date only Helmi et al (2009), who had investigated a one-hectare plot of the upper lowland forest at Bodogol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areal HR di TNGGP terdapat di Resort Nagrak, Resort Gunung Putri dan Resort Bodogol (Handayani et al,2019;Ario et al, 2020) Informasi struktur dan komposisi vegetasi di HA TNGGP telah banyak dilakukan dan dikompilasi oleh Kartawinata dan Sudarmonowati (2022). Untuk vegetasi di HA Bodogol di informasikan oleh Helmi et al (2009), Rozak et al (2016), Junaedi et al (2020) dan Sadili et al (2023a). Dan vegetasi HT Bodogol oleh Arifin (2011), Iskandar (2011), Raharjo (2011, Sadili dan Alhamd (2012), Sadili (2014) dan Sadili et al (2023b).…”
Section: Pendahuluanunclassified
“…Penanaman kembali dilakukan di areal ruang-ruang kosong yang ditumbuhi semak belukar (Gambar 5). Selain jenis yang dapat merangsang hewan penyebar datang, jenis yang digunakan juga menggunakan jenis-jenis kunci, seperti dari famili Fagaceae atau Lauraceae, tetapi diutamakan dari famili Dipterocarpaceae karena di TNGGP famili tersebut berstatus terancam (Junaedi et al, 2020).…”
Section: No Jenis (Species)unclassified